2007
DOI: 10.1007/s00330-007-0734-7
|View full text |Cite
|
Sign up to set email alerts
|

Variability of repeated coronary artery calcium measurements by 1.25-mm- and 2.5-mm-thickness images on prospective electrocardiograph-triggered 64-slice CT

Abstract: High reproducibility on coronary artery calcium scoring is a key requirement in monitoring the progression of coronary atherosclerosis. The purpose of this prospective study is to assess the reproducibility of 1.25-mm- and 2.5-mm-thickness images on prospective electrocardiograph-triggered 64-slice CT with respect to 2.5-mm-thickness images on spiral overlapping reconstruction. One hundred patients suspected of coronary artery disease were scanned twice repeatedly, both on prospective electrocardiograph-trigge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 32 publications
1
14
1
Order By: Relevance
“…However, it was also reported that the increase in detection threshold lead to false-negative scoring results in 6 patients [29]. Similar results of improved calcium detection with thinner slices were found for other studies [9, 22, 31, 32]. However, these studies analysed the effect of thin-slice reconstructions predominantly in patients with positive calcium scores, whereas in the present study, the effect of thin-slice reconstructions focused on 100 patients with and 100 patients without coronary calcium at standard 3.0 mm reconstructions.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…However, it was also reported that the increase in detection threshold lead to false-negative scoring results in 6 patients [29]. Similar results of improved calcium detection with thinner slices were found for other studies [9, 22, 31, 32]. However, these studies analysed the effect of thin-slice reconstructions predominantly in patients with positive calcium scores, whereas in the present study, the effect of thin-slice reconstructions focused on 100 patients with and 100 patients without coronary calcium at standard 3.0 mm reconstructions.…”
Section: Discussionsupporting
confidence: 79%
“…For calculating the Agatston score, a weighing factor is applied based on the peak attenuation within a calcified lesion. This may lead to a higher variability than with the volume score or calcium mass [9]. However, large clinical risk stratification studies are based on the Agatston score [3, 4, 10].…”
Section: Introductionmentioning
confidence: 99%
“…First, CAC scoring on low-dose ungated MDCT scans may not be familiar to most CAC readers. We found, however, that with a training session, interobserver variability was not particularly high compared with that reported for regular cardiac CT [22,23]. Second, it is unknown whether our findings can be reproduced on scanners made by other manufacturers.…”
Section: Cac In Ct Lung Cancer Screeningcontrasting
confidence: 73%
“…The same effect was also observed in studies with 16‐slice MDCT comparing 1–3 mm (38). Reduced measurement errors were also reported for 0.625 compared with 1.25 and 2.5 mm slice thickness using 16‐slice MDCT (29).…”
Section: Discussionmentioning
confidence: 91%